Queen of Ants In the Qur'an Surah An-Naml verse 18 - Akrom, Muhammad Fatih Kanzul; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
The discussion of ants in the Qur'an is found in surah an-Naml verse 18. This critical study of ants is found in the context of language discussion and laboratory research. The beginning of the spirit of rise in this discussion was a critical study of the translation of the meaning of Namlatun which translates to